Performance Insulator Cover Type : YSL-70-AP Post Voltage Break Down Test - Wayan Jondra; IGS Widharma; Nengah Sunaya (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
Electrical energy affect to economic, electrical energy consumption will increase and decrease likely economics. In this globalization era, electricity consumption was increased trend yearly since industrialization era. The reliability Electrical energy is very important for economic growth. The lower SAIDI and SAIFI is the bench mark for reliability of electrical energy supply. The reliable of insulator cover type: YSL-70-AP affect to the reliability electrical distribution energy on over head distribution circuit. Insulator cover protected to over head distribution circuit againt animal, bird, tree ang other temporary disturbance. Insulator cover also to protect half insulated medium voltage cable againt partial discharge and flashover. Over voltage stress more often during operation, to impact to the material insulation performance. This quantitative research founding: insulator cover type: YSL-70-AP still feasible to use after voltage breakdown stress. The fault current is still under the maximum allowable leakage current (11,600 micro ampere) which is 41.61 micro ampere, and breakdown voltage is still higher than minimum that specified (24 kilo volt), which is 49.63 kilo volt. Post breakdown voltage the material insulation performance of insulator cover type: YSL-70-AP is good, and reliable to continuous operation over head distribution circuit.